Qualitative Research and Data Support: The Jan Brady of Social Sciences Data Services? - Swygart-Hobaugh, Amanda J. (2016)
This chapter gives an overview of the context of qualitative data and the resulting support needs of qualitative researchers at various stages of the research data lifecycle. The current state of qualitative data support services in social sciences librarianship is then explored by reporting on (1) an analysis of social sciences data librarian job postings, (2) a survey of social sciences librarians, and (3) an examination of online research guides describing qualitative data support services presently offered by social sciences librarians. Finally, this chapter concludes with recommendations for how social sciences librarians might embark on the expansion of their qualitative data support services. Additional information about the book is available at https://databrarianship.wordpress.com